Mitophagy in degenerative joint diseases. Issue 9 (2nd September 2021) - Sun, Kai; Jing, Xingzhi; Guo, Jiachao; Yao, Xudong; Guo, Fengjing
ABSTRACT: Mitochondrial dysfunction is involved in aging and multiple degenerative diseases, including intervertebral disc degeneration (IVDD) and osteoarthritis (OA). Thus, the maintenance of mitochondria homeostasis and function is important. Mitophagy, a process that selectively clears damaged or dysfunctional mitochondria through autophagic machinery, functions to maintain mitochondrial quality control and homeostasis. IVDD and OA are similar joint diseases involving the degradation of cartilaginous tissues that are mainly caused by oxidative stress, cell apoptosis and extracellular matrix (ECM) degradation. Over the past decade, accumulating evidence indicates the essential role of mitophagy in the pathogenesis of IVDD and OA. Importantly, strategies by the regulation of mitophagy exert beneficial effects in the pre-clinical experiments. Given the importance and novelty of mitophagy, we provide an overview of mitophagy pathways and discuss the roles of mitophagy in IVDD and OA. We also highlight the potential of targeting mitophagy for the treatment of degenerative joint diseases. Abbreviations: AD: Alzheimer disease; AF: annulus fibrosus; ADORA2A/A2AR: adenosine A2a receptor; AMBRA1: autophagy and beclin 1 regulator 1; BMSCs: bone marrow mesenchymal stem cells; BNIP3: BCL2 interacting protein 3; BNIP3L/NIX: BCL2/adenovirus E1B interacting protein 3-like; CDH6: cadherin 6; CEP: cartilaginous endplates; circRNA: circular RNA; DNM1L/DRP1: dynamin 1-like; ECM: extracellular matrix; HIF1A: hypoxia inducible factor 1: alpha subunit; IL1B: interleukin 1 beta; IMM: inner mitochondrial membranes; IVDD: intervertebral disc degeneration; MAPK8/JNK: mitogen-activated protein kinase 8; MFN1: mitofusin 1; MFN2: mitofusin 2; MIA: monosodium iodoacetate; RHOT/MIRO: ras homolog family member T; MMP: mitochondrial transmembrane potential; CALCOCO2/NDP52: calcium binding and coiled-coil domain 2; NFE2L2: nuclear factor: erythroid 2 like 2; NP: nucleus pulposus; OA: osteoarthritis; OPA1: OPA1: mitochondrial dynamin like GTPase; OPTN: optineurin; PRKN: parkin RBR E3 ubiquitin protein ligase; PD: Parkinson disease; PGAM5: PGAM family member 5; PPARGC1A/PGC-1A: peroxisome proliferator activated receptor: gamma: coactivator 1 alpha; PHF23: PHD finger protein 23; PINK1: PTEN induced putative kinase 1; ROS: reactive oxygen species; SfMSCs: synovial fluid MSCs; SIRT1: sirtuin 1; SIRT2: sirtuin 2; SIRT3: sirtuin 3; SQSTM1/p62: sequestosome 1; TNF: tumor necrosis factor; Ub: ubiquitin; UBL: ubiquitin-like; VDAC: voltage-dependent anion channel.